Urinary continence following extraperitoneal radical prostatectomy: impact of surgical technique and pelvic fascial spaces reconstruction - M. B. Chibichyan; M. I. Kogan; I. I. Belousov; D. V. Sizyakin; A. V. Avetyan; P. V. Trusov; S. V. Shkodkin; A. S. Pchelkin (Вестник урологии, 2024)
Introduction. Urinary incontinence is a common complication of radical prostatectomy. The development of surgical techniques when performing radical prostatectomy that improve the function of urinary continence after surgery is actual.Objective. To compare urinary continence functions in long-term follow-up after open and laparoscopic radical prostatectomy when only posterior or combined (anterior + posterior) reconstruction of the pelvic fascial spaces is performed.Materials & methods. The study included 130 patients aged 63.0 [59.0; 68.0] years with local prostate cancer (сT1a-2сN0-xM0; 1 – 4 ISUP groups), subjected to non-nerve-sparing retropubic radical prostatectomy with posterior reconstruction and non-nerve-sparing extraperitoneal laparoscopic radical prostatectomy with isolated posterior or combined (anterior + posterior) fascial reconstruction of the pelvic fascial spaces. Postoperative continence function was studied at 1, 3, 6, and 12 months following surgery using a standard pad test.Results. The incidence of urinary continence was higher at all follow-up periods during laparoscopic surgery. From the 6-months follow-up, these patients did not have severe urinary incontinence. At the same time, the rate of growth of some patients who began to retain urine did not depend on the method of reconstruction of the pelvic fascial spaces. The use of combined reconstruction of the pelvic fascial spaces at 12-months follow-up showed an advantage in urinary continence over performing only posterior reconstruction. Such patients achieved urinary continence in 90% of cases compared to 80.0% of cases. At the same time, the restoration of urinary continence at all periods of observation had a relatively uniform linear rate of increase in the indicator.Conclusion. Reconstruction of the pelvic fascial spaces during open and laparoscopic radical prostatectomy allows one to achieve satisfactory continuation in the postoperative period. However, higher efficiency is achieved when using a combined reconstruction technique.